Business Continuity During The Transition To Renewable Energy: A Qualitative Study of Operational And Financial Risks Management - Rangga Punta Raihanda; M. Devitia Putri Nilamsari (ACCRUALS (Accounting Research Journal of Sutaatmadja), 2026)
This study aims to identify the operational and financial risks affecting the business continuity of PT Batara Batari Sinergy Nusantara during the renewable energy transition and to analyze the company’s risk management practices. The energy transition creates uncertainty for coal trading companies, particularly regarding supply stability, commodity quality, financing, and cash flow pressure. This research adopts a qualitative approach using a case study method. Data were collected through in-depth interview with the director and relevant staff, supported by a literature review. Data analysis was conducted using the ISO 31000 risk management framework, which includes risk identification, analysis, evaluation, and treatment. The findings indicate that the company faces operational risks related to biomass supply instability, biomass quality, and social risks along transportation routes, and financial risks such as limited financing, declining profit margins, and long payment cycles. Biomass quality and social risks are classified as high to very high risks requiring immediate mitigation. The company addresses these risks through strengthened quality control, supplier development, cash flow management, funding diversification, and product diversification into biomass. These findings demonstrate that ISO 31000-based risk management, supported by the company’s dynamic capabilities, plays a critical role in maintaining business continuity amid the energy transition.